Evaluation on role of the chest pain nurse in emergency management of patients with ST-elevation myocardial infarction (专职胸痛护士在ST段抬高型急性心肌梗死患者急救中的应用研究) - QIAN Hongmei (钱宏梅); WEI Yingying (韦莹莹); WANG Yan (王艳) (Association of Integrative Nursing, 2021)
Objective To explore the role of chest pain nurse in the emergency management of patients with ST-elevation myocardial infarction (STEMI). Methods Basing on the requirement of chest pain center construction, a group of chest pain full-time nurses were recruited in emergency room and catheter room for Digital subtraction angiography (DSA), and the emergency care process of STEMI patients was modified. A total of 60 cases in control group adopted routine emergency care mode, and another 58 cases in the experimental group adopted modified emergency care model. The time period of key interventions in the process of emergency management were calculated. Results The duration between hospital admission and admission to the emergency room, between hospital admission and first ECG diagnosis, between clinical admission and blood draw for cardiac troponin T test, cardiac troponin T test, between hospital admission and emergency room discharge, between catheterization room activation and catheterization room admission, between catheterization room admission and onset of PCU, Door-to-Balloon Time (D2B) in the experimental group was shorter than that in the control group, respectively (P＜0. 05). Conclusion In the emergency management of STEMI patients, the establishment of chest pain nurses are helpful to shorten the period first aid in hospital, improve the efficiency of emergency treatment. (目的 探讨专职胸痛护士在ST段抬高型心肌梗死(STEMI)患者急救中的作用。方法 基于胸痛中心建设要求, 通过在急诊室、导管室设立专职胸痛护士岗, 优化STEMI患者急救护理流程, 对流程优化前2019年1月-10月(对照组60例)和流程优化后2020年1月-10月(研究组58例)STEMI患者的相关救治节点时间进行比较。结果 研究组患者入门-抢救室接诊时间、入门-首份心电图诊断时间、接诊-肌钙蛋白抽血时间、肌钙蛋白抽血-肌钙蛋白报告时间、入门-离开急诊时间、导管室激活-到达导管室时间、到达导管室-PCI造影开始时间、门诊-首次球囊扩张(D2B)时间均短于对照组, 差异有统计学意义(P＜0. 05)。结论 在STEMI患者急救中, 设立专职胸痛护士有助于改善STEMI患者院内急救延误环节, 提高急救效率。)